Contribution of Forestry in Economy and Employment Generation in Nepal - Yamuna Paudel; Ashish Paudel (Indonesian Journal of Social and Environmental Issues (IJSEI), 2021)
The forestry sector provides a vast array of goods and services to mankind. Goods and services like timber, medicine, fodder, tourism carbon sequestration, and soil and water conservation were used by people from early ages. But its contribution hasn’t been accounted for properly. The study is aimed at collecting data on the contribution of the forestry sector to the national economy and employment generation in Nepal.  Data on the economy and employment contribution were collected from reviewing the literature, Nepal government's annual reports. At present agriculture and forestry sector contributes about 27% to the national GDP. Among different forest products timber is regarded as major production to earn royalty inside the country that Nepal government earned a royalty of NRs 279.9 million from annual production of 10.2 million cubic feet timber in the fiscal year 2019/2020. But non-timber forest product is regarded as the main forest product which is exported from the country that Nepal exported medicinal plants of US$6.48 million in 2016. Over 150,000 people are employed in timber-based manufacturing industries. The government institutions have provided around 143,000 employment in the forestry-related sector. Having high potentiality of contributing to job formation and income generation still forestry sector has not been regarded as a major sector of national income. Its contribution has not been accurately calculated which has underestimated the economic value of the forest. Hence, there is a need for the formation of proper valuation techniques and practice of keeping good market records of the utilization of natural resources and employment generation.